Romulus et Rémus, Pierre et Paul: Du fratricide à la concorde fraternelle - Briquel, Dominique (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
Ancient authors present the founding of Rome as done either by one conditor, Romulus, or by two conditores, Romulus and Remus. Use of singular or plural was not really significant, as everyone knew that the twin brothers had a different destiny and that Rome was founded, as such, by Romulus alone. But use of the plural conditores as founders of the city is common in Christian texts: it was a way for Christian authors to emphasize that from its very beginnings Rome was affected by crime of the most scandalous sort, Romulus killing his own brother. By contrast Christians could find in their own tradition a model of perfect brotherhood, or at least brotherhood in Christ, viz. Peter and Paul, who were the common founders of Roma Christiana. Peter and Paul were the figures that Christians could set against Romulus and Remus, as founders of the new Christian city.